Charles Blagden in revolutionary America: two unpublished letters to John Lloyd. (16th August 2017) - Frame, Paul
Abstract : Prior to becoming a secretary of the Royal Society in 1784 Charles Blagden ( bapt . 1748– d . 1820) served as a surgeon in the British army during the Revolutionary War in America. In the two unpublished letters of 1778 discussed here, Blagden provides his Welsh friend John Lloyd (1749–1815) with a vivid description of the current state of affairs in America, from a British perspective, and with insights into continuing scientific endeavour in a time of war. The letters illustrate the attempt that two men made to keep alive an intellectual life and are testimony to the rapidity with which matters of scientific interest could be disseminated in the eighteenth century, even during a major international conflict.